Leadership skills assessment of Filipino librarians in the National Capital Region(NCR) - Yao, Bryan Jerahmeel G. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
In the field of Library and Information Science (LIS), both foreign and local studies show that there is a need for more leaders in the field. In the Philippines, the Professional Regulatory Board for Librarians (PRBFL) sent a team to conduct monitoring visits in different libraries in the country. However the team seldom encountered plans that include visions, goals, and strategies. Moreover, some librarians had no motivation to work, and had no skills to influence administrators for the improvement of their libraries.